PENGARUH CEKAMAN AIR PADA DUA JENIS TANAH TERHADAP PERTUMBUHAN DAN HASIL KEDELAI ( Glycine max (L.) MERRIL) - Nurhayati Nurhayati (Jurnal Floratek, 2009)
Effect of Water Stress at Two Types of Soil on Growth and Yield of Soybean  (Glycine max (L.) MERRIL) Nurhayati Fakultas Pertanian Unsyiah, Darussalam Banda Aceh ABSTRACT  This study was aimed at determining effect of water stress maintained at 100, 80, 60, and 40% of field capacity in ordo Entisol and Ultisol on growth and yield of soybean. Experimental design used was a completely randomized design, 4 x 2 with three replicates. Results showed that water stress significantly affected all components of growth and yield of soybean, as well as amount of cumulative water need of soybean at plant ages of 8 - 95 days. Soil type also significantly affected all components of growth and yield of soybean, as well as amount of cumulative water need of soybean, except root length.  The best growth and yield of soybean was found at ordo Entisol. There was a highly significant interaction of all components of soybean growths and yields, except plant height at the age of 15 and 30 days after planting.  Soybean was still capable of producing high yield at the range of water stress 60% - 80% of field capacity in ordo Entisol, whereas in ordo Ultisol at the same circumstance, the soybean was not capable of maintaining the yield.